Man against machine: diagnostic performance of a deep learning convolutional neural network for dermoscopic melanoma recognition in comparison to 58 dermatologists - Hänßle, Holger; Müller-Christmann, Christine; Schneiderbauer, Roland; Toberer, Ferdinand; Enk, Alexander; Uhlmann, Lorenz (Annals of oncology, 2018)
AbstractBackground. Deep learning convolutional neural networks (CNN) may facilitate melanoma detection, but data comparing a CNN’s diagnostic performance to l
Gesehen am 20.08.2019